68 The impact of advance care planning on dying in hospital. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Callender, Thomas; Riley, Julia; Wiggins, Natasha; Archer, Stephanie; Droney, Joanne
Abstract : Background: Fewer than half of patients opt to die in hospital, yet this remains the most common place of death in England. Coordinate My Care (CMC) is London's Electronic Palliative Care Coordination Service. Previous analysis has shown that individuals with a 'do not resuscitate' order shared through CMC are 76% more likely to die in a place of their choosing, however the relationship between a recorded preferred place of death (PPD) and death outside of hospital is unknown. Enabling individuals to die outside of hospital is an indicator of quality in end of life care, and a cost-saving strategy. Aims: To analyse the relationship between documentation of a preferred place of death and resuscitation status on the likelihood of death in hospital. Methods: Retrospective cohort study of all adults with a CMC plan made between 31 st March 2011 and 31 st September 2016 with a recorded place of death. We explored the cohort with standard descriptive statistics before using multiple imputation by chained equations and multivariable logistic regression. Results: Of all 11 839 persons, 1% with a recorded PPD wished to die in hospital. Those missing a PPD were 80% more likely to die in hospital (OR, 95% CI: 1.80, 1.61 to 2.01, p<0.001; 31% vs 14%), whilst those who were 'for resuscitation' were 89% more likely to die in hospital (OR, 95% CI: 1.89, 1.69 to 2.13, p<0.001; 30% vs 13%). Those missing one aspect of advance care planning were more likely to be either for resuscitation or to have no recorded preferred place of death, respectively. Conclusions: Advance care planning in the form of shared PPD and resuscitation status is significantly associated with dying outside of hospital. These discussions should be offered to those at the end of life, and shared with relevant healthcare professions involved in an individual's care.